Comprehensive structure-selective characterization of dissolved organic matter by reducing molecular complexity and increasing analytical dimensions. (1st December 2016) - Li, Yan; Harir, Mourad; Lucio, Marianna; Gonsior, Michael; Koch, Boris P.; Schmitt-Kopplin, Philippe; Hertkorn, Norbert
Abstract: Deciphering the molecular codes of dissolved organic matter (DOM) improves our understanding of its role in the global element cycles and its active involvement in ecosystem services. This study demonstrates comprehensive characterization of DOM by an initial polarity-based stepwise solid phase extraction (SPE) with single methanol elution of the cartridges, but separate collection of equal aliquots of eluate. The reduction of molecular complexity in the individual DOM fractions attenuates intermolecular interactions and substantially increases the disposable resolution of any structure selective characterization. Suwannee River DOM (SR DOM) was used to collect five distinct SPE fractions with overall 91% DOC recovery. Optical spectroscopy (UV and fluorescence spectroscopy), high-field Fourier transform ion cyclotron mass spectrometry (FTICR MS) and nuclear magnetic resonance (NMR) spectroscopy showed analogous hierarchical clustering among the five eluates corroborating the robustness of this approach. Two abundant moderately hydrophobic fractions contained most of the SR DOM compounds, with substantial proportions of aliphatics, carboxylic-rich alicyclic molecules, carbohydrates and aromatics. A minor early eluting hydrophilic fraction was highly aliphatic and presented a large diversity of alicyclic carboxylic acids, whereas the two late eluting, minor hydrophobic fractions appeared as a largely defunctionalized mixture of aliphatic molecules. Comparative mass analysis showed that fractionation of SR DOM was governed by multiple molecular interactions depending on O/C ratio, molecular weight and aromaticity. The traditional optical indices SUVA254 and fluorescence index (FI) indicated the relative aromaticity in agreement with FTICR mass and NMR spectra; the classical fluorescent peaks A and C were observed in all four latter eluates. This versatile approach can be easily expanded to preparative scale under field conditions, and transferred to different DOM sources and SPE conditions. Graphical abstract: Highlights: A stepwise SPE-based fractionation reduced DOM molecular complexity. DOM fractionation was distinct from customary LC-based methods. Attenuated intermolecular interactions improved FTICR MS and NMR resolution. DOM fractions clustered alike in optical spectroscopy, FTICR mass and NMR spectra. This versatile fractionation is amenable for preparative field work conditions.